Agave americana (Ketuke) toxicity in the kidney of Clarias batrachus - Prasad, Archana; Puri, Rukmini (Journal of Natural History Museum, 2018)
Different parts of plant have been used since many decades by humans for catching fishes. In this investigation, ‘ketuke ‘leaf effect was observed on behavioral change and histological alterations in the kidney of Clarias batrachus. Few fishes were kept as control i.e. not exposed to plant piscicide. The other fishes were exposed to 3gm per 30 liters of water for 24 and 48 hrs. In exposed fish’s restlessness, vigorous movement, excessive secretion of slime and loss of appetite was seen. Histologically, glomerular contraction, clumping of melanomacrophages, degeneration of epithelial tissue along with the degeneration of renal tubules and others were seen. Increase in the Bowman’s space was one of the noticeable changes. Extract accumulation was seen in the tissues. Exposure to sub lethal concentrations of Ketuke (Agave americana), caused duration dependent histopathological alterations in the kidney of Clarias batrachus which is discussed in the paper.